Tragedy, philosophy, and political education in Plato's laws - Balot, Ryan K. (Oxford University Press, 2024)
"What are the prospects for ambitious political reform in communities of traditional, passionate, and even self-righteous citizens? Can thoughtful legislators create a healthy society for citizens whose judgment is typically unsound? In a searching and provocative analysis, Ryan Balot addresses these timely - though universal - political questions by offering a novel interpretation of Plato's Laws. Turning to the ancient past is essential to reinvigorating our contemporary understanding of these all-important issues. Previous readers have either celebrated the work's idealism or denounced its totalitarianism. Balot, by contrast, refuses to interpret the dialogue as a political blueprint, whether admirable or misguided. He shows instead that it constitutes Plato's greatest philosophical investigation of political life. In this transformative re-appraisal, Balot reveals that Plato's goal was to cultivate a tragic attitude toward our political passions, commitments, and aspirations. The result is a profound political inquiry with far-reaching consequences"--